1987
DOI: 10.1021/bk-1987-0330.ch021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phytochemistry in Attacking the Leafy Spurge (Euphorbia esula) Problem

Abstract: Individual chemical constituents isolated and char acterized from the noxious weed Euphorbia esula were assessed biologically and/or chemotaxonomically in relation to the allelopathy of E. esula, the allelopathy of Antennaria microphylla to E. esula, and the insect biological control of E. esula. Kaemferol 3-glucuronide and 1-hexacosanol obtained from aqueous extracts of E. esula are considered important allelochemicals in this weed. Biological assays, utilizing E. esula test systems, support hydroquinone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…7 Two slightly different methylated ellagic acids (3,3',4-tri-O-methyl and 3,4,4'-tri-O-methyl) from those we found have been reported to be inhibitors of auxin transport in chestnut root cuttings, perhaps accounting for the difficulty of obtaining chestnut plants from root cuttings. 19 The decreased root branching we observed when Arabidopsis was treated with ellagic acid (and derivatives) might arise from a similar mechanism.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…7 Two slightly different methylated ellagic acids (3,3',4-tri-O-methyl and 3,4,4'-tri-O-methyl) from those we found have been reported to be inhibitors of auxin transport in chestnut root cuttings, perhaps accounting for the difficulty of obtaining chestnut plants from root cuttings. 19 The decreased root branching we observed when Arabidopsis was treated with ellagic acid (and derivatives) might arise from a similar mechanism.…”
Section: Discussionmentioning
confidence: 58%
“…5 Studies of leafy spurge biochemistry have identified several phytotoxins, including the relatively strong phytotoxins kaempferol-3-glucuronide and 1-hexaconsanol in aqueous extracts of the whole plant, 6 and moderately phytotoxic esulone jatrophane diterpenes in leafy spurge roots. 7,8,9 However, in a comparison of ether extracts of leafy spurge roots from North Dakota, Montana, Oregon, and Austria (where the leafy spurge is not a problem weed), only the North Dakota samples had high concentrations of jatrophane diterpenes. 9 3,3'-Di-O-methylellagic acid 4-b-D-xyloside and 3,3'-di-O-methylellagic acid 4-D-glucoside have also been isolated from leafy spurge roots, but the phytotoxicity of these compounds has not been assessed due to poor solubility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 7500 species of Euphorbiaceae, many are known as weeds that exert allelopathic activity on crops. The allelopathic potential of extracts, residues and root secretions of Euphorbia corollata L. (Rice, 1964), E. esula L. (Manners, 1987), E. geniculata Ortega (Sugha, 1979), E. granulata Forssk (Hussain, 1980), E. hirta L. (Tiwari et al, 1985), E. prostrata Aiton (Alsaadawi et al, 1990), E. hierosolymitana Boiss. (Abu-Romman et al, 2010) and E. helioscopia L. (Qasem, 1995;Tanveer et al, 2010) have been reported against crops like pea, tomato, wheat, chickpea, cotton, alfalfa, lettuce, groundnut, and soybean.…”
mentioning
confidence: 99%
“…Elmore & Paul (1983) reported high concentration of phenolics in E. supina and E. maculata, which is supported by previous findings of Rice (1969), who reported phenolics and gallic acid in E. supine. Wanger et al, (1970), Manners & Wong (1985), Manners (1987), Manners & Davis (1987) and Qin et al (2006) have identified several phototoxins, including relatively strong phytotoxins Kaempferol-3-glucuronide and I-hexaconsanol in aqueous extracts of the whole plant, and moderately diterpenes jatrophane in leafy spurge roots. Euphorbia esula (Evans & Kinghorn, 1977;Roberts & Olson, 1999;Zhi Qiang et al, 2008) and E. heliescopia (Jiangbo et al, 2010) contains di-and tri-terpenoids and condensed tannins.…”
Section: Allelochemicals In Euphorbia Speciesmentioning
confidence: 99%